PEMBERDAYAAN KADER PEMBERDAYAAN MASYARAKAT MELALUI MODEL MANAJEMEN PROYEK BERBASIS KOMITE - Bahdin Nur Tanjung; Melisa Nur Asima Sidabutar; Lusi Febriyami Sitompul (Yayasan Nusantara Hasana Berdikari, 2024)
This Community Empowerment (PkM) activity aims to enhance the capacity of community empowerment cadres to plan, implement, and evaluate community programs through the application of a committee-based project management model. Challenges frequently faced by cadres include unclear role distribution, coordination among stakeholders, basic budget management, activity documentation, as well as unstructured reporting and evaluation. The program is implemented through needs assessments, core project management training (planning, scheduling, budgeting, risk management), the formation of project committees and governance structures (RACI), the development of SOPs and project administration templates, implementation simulations, and mentoring for the implementation of pilot projects at the community level. Outputs include a project document package (TOR, work plan, budget estimate, risk register, logbook, reports), a project committee structure, and a simple monitoring dashboard. The expected outcomes are increased accountability, improved program implementation effectiveness, and the sustainability of community-based activities.